2015
DOI: 10.5252/g2015n1a1
|View full text |Cite
|
Sign up to set email alerts
|

Évolution lithostratigraphique, paléoenvironnementale et paléogéographique du flysch de Ben-Zireg (Viséen inférieur, Algérie)

Abstract: La structure anticlinale de Ben-Zireg se situe sur la marge nord-occidentale de la plate-forme saharienne. Sur le flanc nord de cette structure affleure une formation silicoclastique attribuée au Viséen inférieur, dénommée « flysch de Ben-Zireg ». Sur une épaisseur d'environ 400 m, cette formation peut être divisée en quatre grands ensembles : 1) le « pré-flyschoïde » formé d'une alternance de pélites et de bancs de grès à « HCS », dans laquelle s'intercalent des niveaux calcaires bioclastiques. Ce premier ens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 35 publications
1
11
0
Order By: Relevance
“…2) on the Saharan craton to the south. Similar sections are found farther eastward in Algeria, in the Bechar area (BENYOUCEF et al, 2012(BENYOUCEF et al, , 2014. All these data suggest that a South to North dipping (Tethyan-oriented), lowgradient ramp also existed on the Algerian side of the western Saharan craton in Cenomanian times.…”
Section: Kem Kem Embayment and Bechar Area In Algeriasupporting
confidence: 56%
See 1 more Smart Citation
“…2) on the Saharan craton to the south. Similar sections are found farther eastward in Algeria, in the Bechar area (BENYOUCEF et al, 2012(BENYOUCEF et al, , 2014. All these data suggest that a South to North dipping (Tethyan-oriented), lowgradient ramp also existed on the Algerian side of the western Saharan craton in Cenomanian times.…”
Section: Kem Kem Embayment and Bechar Area In Algeriasupporting
confidence: 56%
“…Cenomanian deposits are only known on the shoulders of the two branches of the rift. In these eastern areas, the map is constructed from the works of CISZAK et al (1999) and HADDOUMI et al (2008HADDOUMI et al ( , 2010 in the Middle Atlas, of ETTACHFINI et al (2005) and LÉZIN et al (2012) on the southern border of the High-Atlas in eastern Morocco, and from BENYOUCEF et al (2014) in the Bechar area (Saharan platform, western Algeria). Stratigraphic data from CAVIN et al (2010) and satellite images are used to delineate the Kem Kem embayment.…”
Section: Palaeogeographic Contextmentioning
confidence: 99%
“…(1992); 17 Hollard et al, (1985); 18 Benyoucef et al. (2015); 19 Zouhri et al. (2008); 20 Arantegui et al.…”
Section: From Time‐temperature Models To Source‐to‐sink Maps: Workflomentioning
confidence: 99%
“…Extensive palaeontological work has also shown that the clastics overlying basement in parts of the Anti-Atlas are Cenomanian in age (Late Cretaceous; e.g. Benyoucef et al, 2015). In the central Anti-Atlas, no recent biostratigraphic study on the undifferentiated Mesozoic clastic sediments has been conducted, but the Cenomanian limestones positioned higher in the stratigraphic column can be F I G U R E 5 Digitized t-T modelling weighted averages for considered regions (a-i), best-fit curves and acceptable envelopes (grey area) for HeFTy results or expected curves, maximum likelihood curves and limits of 2σ confidence level (grey area) for QTQt results (see references in Table 1).…”
Section: Geological Constraintsmentioning
confidence: 99%
See 1 more Smart Citation